Holes eaudiobook - Sachar, Louis (Holes, 2006)
This groundbreaking classic is now available in a special anniversary edition with bonus content. Winner of the Newbery Medal as well as the National Book Award, HOLES is a New York Times bestseller and one of the strongest-selling middle-grade books to ever hit shelves! Stanley Yelnats is under a curse. A curse that began with his no-good-dirty-rotten-pig-stealing-great-great-grandfather and has since followed generations of Yelnatses. Now Stanley has been unjustly sent to a boys' detention center, Camp Green Lake, where the boys build character by spending all day, every day digging holes exactly five feet wide and five feet deep. There is no lake at Camp Green Lake. But there are an awful lot of holes. It doesn't take long for Stanley to realize there's more than character improvement going on at Camp Green Lake. The boys are digging holes because the warden is looking for something. But what could be buried under a dried-up lake? Stanley tries to dig up the truth in this inventive and darkly humorous tale of crime and punishment —and redemption. Special anniversary edition bonus content includes: A New Note From the Author!; "Ten Things You May Not Know About HOLES" by Louis Sachar; and more!